2021
DOI: 10.5713/ab.21.0006
|View full text |Cite
|
Sign up to set email alerts
|

The role of long noncoding RNAs in livestock adipose tissue deposition

Abstract: With the development of sequencing technology, numerous , long noncoding RNAs (lncRNAs) have been discovered and annotated. Increasing evidence has shown that lncRNAs play an essential role in regulating many biological and pathological processes, especially in cancer. However, there have been few studies on the roles of lncRNAs in livestock production. In animal products, meat quality and lean percentage are vital economic traits closely related to adipose tissue deposition. However, adipose tissue accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…However, a future application can certainly expand it to additional features, such as (4 4 + 4 5 + 4 6 + 4 7 ), to enhance the discrimination specificity and sensitivity when genomes become complex. A recent study used motifs 4 6 and 4 7 to select biologically significant motifs in the human genome 33 …”
Section: Discussionmentioning
confidence: 99%
“…However, a future application can certainly expand it to additional features, such as (4 4 + 4 5 + 4 6 + 4 7 ), to enhance the discrimination specificity and sensitivity when genomes become complex. A recent study used motifs 4 6 and 4 7 to select biologically significant motifs in the human genome 33 …”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are transcripts longer than 200 nucleotides that lack a protein-coding ability but some can encode small peptides [ 9 ]. Previous studies focused on fat metabolism revealed that lncRNAs potentially regulate multiple biological processes, such as preadipocyte differentiation, fat cell differentiation and IMF deposition [ 10 ]. The intramuscular fat-associated long non-coding RNA (lncRNA IMFNCR ) acts as a molecular sponge to bind to miR-128-3p and miR-27b-3p, thereby increasing the expression of the peroxisome proliferator-activated receptor γ ( PPARγ ) and promoting fat cell differentiation and IMF deposition in chicken muscle [ 11 ].…”
Section: Introductionmentioning
confidence: 99%